2013
DOI: 10.2217/pgs.13.217
|View full text |Cite
|
Sign up to set email alerts
|

BDNF rs6265 Polymorphism and Drug Addiction: a Systematic Review and Meta-Analysis

Abstract: A majority of studies have shown a link between the common functional rs6265 polymorphism of the BDNF gene and susceptibility to drug dependence. However, the pattern of results is inconsistent. To precisely evaluate this association, a systematic review and meta-analysis of previous case-control reports was conducted. Data from 20 studies containing 9419 participants (4665 cases and 4754 controls) conducted between 2004 and 2013 restricted to alcohol, nicotine, heroin, substance and methamphetamine dependency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 54 publications
2
28
2
3
Order By: Relevance
“…craving for larger doses), and painful withdrawal 1,2. This disorder is a global healthcare burden and contributes toward serious behavioral, medical, psychiatric, and social consequences 3. In response to continued opiate administration, several long-term structural and biochemical alterations occur in the brain that can be explained collectively as neuroplasticity or neuroadaptations 4.…”
Section: Introductionmentioning
confidence: 99%
“…craving for larger doses), and painful withdrawal 1,2. This disorder is a global healthcare burden and contributes toward serious behavioral, medical, psychiatric, and social consequences 3. In response to continued opiate administration, several long-term structural and biochemical alterations occur in the brain that can be explained collectively as neuroplasticity or neuroadaptations 4.…”
Section: Introductionmentioning
confidence: 99%
“…BDNF has a functional polymorphism (rs6265, val66met) that has been widely studied in schizophrenia [11] and drug addiction [12]. Associations with METH dependence have been reported [13,14], albeit not in all ethnic groups [15,16], as well as with responses to amphetamine infusion [17].…”
mentioning
confidence: 99%
“…Therefore, the BDNF Val66Met gene polymorphism may not contribute to susceptibility to heroin abuse. On the other hand, a recent meta-analysis showed that Val allele was a risk factor for heroin dependence [60]. In Han Chinese, Val carriers were associated with heroin addiction and early onset of heroin use [61].…”
Section: Discussionmentioning
confidence: 99%